2015
DOI: 10.21161/mjm.70315
|View full text |Cite
|
Sign up to set email alerts
|

A novel putative non-ligninolytic dehalogenase activity for 3-chloropropionic acid (3CP) utilization by Trichoderma asperellum strain SD1

Abstract: Aims: Trichoderma asperellum strain SD1 grows on 3-chloropropionic acid (3CP), a β-haloalkanoic acid, and produces a putative extracellular dehalogenase that can degrade this acid. Here we further characterized the fungal enzyme system responsible for biodegradation of 3CP. Methodology and results: The primary qualification of the ligninolytic potential in T. asperellum strain SD1 was performed using guaiacol oxidation. When strain SD1 was grown in liquid minimal medium with the presence of 3CP as the sole car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The isolated strain was reported to have outstanding performance in detoxifying L-2-haloacid. Selvamani et al [45] characterized deploying Trichoderma asperellum SD1 to degrade 3-chloropropionic acid in the terrestrial ecosystem. Bagherbaigi et al [46] used Arthrobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated strain was reported to have outstanding performance in detoxifying L-2-haloacid. Selvamani et al [45] characterized deploying Trichoderma asperellum SD1 to degrade 3-chloropropionic acid in the terrestrial ecosystem. Bagherbaigi et al [46] used Arthrobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…The consistent decline in the concentration of 3CP in the growth media with the increase in the incubation time strongly suggested that Burkholderia cepacia was capable of degrading and utilizing the substance as a carbon and energy source. Hence, it is suggested that the ability of Burkholderia cepacia to utilize 3CP in this study may be associated with the existence of a cluster of enzymatic reaction or reactions that favoured the dehalogenation of 3CP (Selvamani et al, 2015). The findings in this study also suggest that the b-dehalogenase in Burkholderia cepacia may have an important role in the degradation of b-chlorinated xenobiotics in the environment.…”
Section: Discussionmentioning
confidence: 52%
“…Most importantly, this strain can ferment the natural materials without pretreatment, showing a great potential in the degradation of natural waste lignocellulosic material (Wang et al 2015;Wang et al 2017). Studies about T. asperellum have reported its potential in glycoside hydrolase (GH) production, and those hydrolases can degrade the carbohydrates in the plant cell walls to release bioactive polymers, proteins, and simple sugars (Selvamani et al 2015).…”
Section: Introductionmentioning
confidence: 99%